Hyperammonemia associated with glycogen storage disease type I - Tunçer, Müyesser; Yalçın, Hüseyin; Özalp, İmran; Çağlar, Melda (The Turkish Journal of Pediatrics, 1982)
Hyperammonemia associated with glycogen storage disease type I is described as a new observation in neonatal secondary hyperammonemias, and the possible contributing effect of hyperammonemia to the clinical signs of glycogen storage disease type I is emphasized.
Keywords: glycogen storage disease; hyperammonemia; hyperuricemia; hypoglycemia; lactic acidemia; newborn